Trends in societal and educational changes generated by the fourth industrial revolution - Bazić, Jovan R (Sociološki pregled, 2018)
This paper discusses the changes in society and education generated by the innovations of the Fourth Industrial Revolution. The basic starting point is that modern technological changes are interdependent with current social processes and development projections that have accelerated their flow. Therefore, this research deals with the analysis of development strategies, information, reports and relevant literature at the document level, and it has applied an analytical and descriptive method to identify and describe the basic factors of technological and change in society and education that generate innovations of the Fourth Industrial Revolution, as well as their interdependence. The innovations of this industrial revolution, as well as the previous ones, simultaneously influence the development and organization of society, its structure and dynamics, the value system, and the everyday life of people.